Genomic insight and physiological characterization of thermoacidophilic Alicyclobacillus isolated from Yellowstone National Park - Kim, Hye Won; Kim, Na Kyung; Phillips, Alex P. R.; Parker, David A.; Liu, Ping; Whitaker, Rachel J.; Rao, Christopher V.; Mackie, Roderick I. (Frontiers in Microbiology, 2023)
Introduction Alicyclobacillus has been isolated from extreme environments such as hot springs, volcanoes, as well as pasteurized acidic beverages, because it can tolerate extreme temperatures and acidity. In our previous study, Alicyclobacillus was isolated during the enrichment of methane oxidizing bacteria from Yellowstone Hot Spring samples. Methods Physiological characterization and genomic exploration of two new Alicyclobacillus isolates, AL01A and AL05G, are the main focus of this study to identify their potential relationships with a thermoacidophilic methanotroph (Methylacidiphilum) isolated from the same hot spring sediments. Results and discussion In the present study, both Alicyclobacillus isolates showed optimal growth at pH 3.5 and 55°C, and contain ω-alicyclic fatty acids as a major lipid (ca. 60%) in the bacterial membrane. Genomic analysis of these strains revealed specific genes and pathways that the methanotroph genome does not have in the intermediary carbon metabolism pathway such as serC (phosphoserine aminotransferase), comA (phosphosulfolactate synthase), and DAK (glycerone kinase). Both Alicyclobacillus strains were also found to contain transporter systems for extracellular sulfate (ABC transporter), suggesting that they could play an important role in sulfur metabolism in this extreme environment. Genomic analysis of vitamin metabolism revealed Alicyclobacillus and Methylacidiphilum are able to complement each other’s nutritional deficiencies, resulting in a mutually beneficial relationship, especially in vitamin B1(thiamin), B3 (niacin), and B7 (biotin) metabolism. These findings provide insights into the role of Alicyclobacillus isolates in geothermal environments and their unique metabolic adaptations to these environments.